Agrochemical methods for increasing the yield of root chicory - O. M. Vyutnova; I. V. Smirnova; I. A. Novikova; K. S. Maksimova (Овощи России, 2023)
Relevance. The effectiveness of fertilizers depends on the need of plants for nutrients and on the ability of the soil to meet this need. According to the Research Institute of Raw Materials of the Alcohol Industry, the responsiveness of chicory to individual substances changes dramatically during the growing season. In the first period of its development, chicory responds sharply positively only to phosphorus. In the future, the phosphorus efficiency remains stable for two months and by the end of the growing season, attenuation begins. The potash efficiency, on the contrary, is low in the first months, and by the end of the growing season, in contrast to the action of phosphorus, it gives a sharp rise. The efficiency of nitrogen during the growing season occupies an average position between the efficiency of phosphorus and potassium.Methodology. The aim of the research was to identify the most effective doses of macro- and microelements and methods of their application (basic and top dressing) to ensure maximum yields of root chicory root crops. The experiments were carried out in the Nonchernozem zone of the Russian Federation in the Rostov district of the Yaroslavl region on the experimental field of the Rostov experimental station for chicory¬ – a branch of the FSBSI FSVC.Results. As a result of the conducted studies, it was found that an increase in the dose of nitrogen nutrition against the background of phosphorus-potassium fertilizer increased the yield of root chicory root crops, fractional application of mineral fertilizers is more effective compared to the main application, the introduction of boron and cobalt increased the content of inulin and sugars in root crops. The inulin content increased as the dose of nitrogen fertilizers increased.